National Institutes of Health Support of Digital Health Behavior Research. (December 2019) - Riley, William T.; Oh, April; Aklin, Will M.; Wolff-Hughes, Dana L.
The National Institutes of Health (NIH) has increasingly supported research in digital health technologies to advance research and deliver behavior change interventions. We highlight some of the research supported by the NIH in eHealth, mHealth, and social media as well as research resources supported by the NIH to accelerate research in this area. We also describe some of the challenges and opportunities in the digital health field and the need to balance the promise of these technologies with rigorous scientific evidence.